2019
DOI: 10.1016/j.jid.2018.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Insights into ZIKV-Mediated Innate Immune Responses in Human Dermal Fibroblasts and Epidermal Keratinocytes

Abstract: Zika virus (ZIKV) has emerged as a global pathogen causing significant public health concern. ZIKV infections in humans principally occur via mosquito bites. Thus, host skin cells are permissive to ZIKV infection and are the first line of defense against the virus. Here, we examined the role and mechanisms of antiviral skin immunity against ZIKV infection. ZIKV infection (African lineage MR766) in human dermal fibroblasts, human epidermal keratinocytes, and HaCaT keratinocytes resulted in distinct expression c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…The preparation of hNPCs was as described previously [12,13]. Briefly, human embryonic stem cells (hESCs) were grown under standard culture conditions with a feeder layer and transferred to a matrigel-coated plate with mouse embryonic fibroblasts (MEFs) conditioned medium.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The preparation of hNPCs was as described previously [12,13]. Briefly, human embryonic stem cells (hESCs) were grown under standard culture conditions with a feeder layer and transferred to a matrigel-coated plate with mouse embryonic fibroblasts (MEFs) conditioned medium.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Total RNA was isolated using Trizol reagent (Invitrogen), as previously reported [13,16]. RNA quality was assessed by Agilent 2100 bioanalyzer using RNA 6000 Nano Chip (Agilent Technologies, Amstelveen, The Netherlands), and RNA quantification was performed using ND-2000 Spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Gene Expression Analysis Using Quantseq 3 Mrna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ZIKV tropism in peripheral tissues was not well characterized yet, clinical studies have shown the viral persistence in several body fluids (21). First’s reports evaluating cell permissiveness demonstrated that ZIKV replicates at placental trophoblasts, endothelial cells, human skin fibroblast and neonatal keratinocytes (21, 35, 36). ZIKV also replicates and induce morphological alterations in human skin explants (35), that are consistent with skin lesions presented in many ZIKV-infected patients (37).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to investigate activity of the cGAS/STING pathway in HaCaTs, a spontaneously immortalized human keratinocyte cell line [57]. This cell line is a good model for primary keratinocytes that serve a barrier function and as host cells for a number of viral infections including papillomaviruses, herpesviruses, mosquito-transmitted alphaviruses and flaviviruses [58][59][60][61][62][63][64], and numerous bacterial and fungal pathogens [65,66]. As not all cell types express every PRR, we sought to ensure the cGAS/STING pathway was functional in HaCaTs and that this pathway was the primary mode of IRF3 phosphorylation in response to foreign DNA.…”
Section: Human Keratinocytes Respond To Foreign Dna Via Cgas/stingmentioning
confidence: 99%